2022
DOI: 10.3390/ijms24010657
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the Proinflammatory Cytokine Genes Modulate the Response to NSAIDs but Not to Triptans in Migraine Attacks

Abstract: Migraine is a common neurovascular disorder characterized by recurrent episodes of headache and associated neurological symptoms. At present, a significant portion of patients do not obtain a satisfactory response to acute pain-relieving therapies, including NSAIDs and triptans. In this context, pharmacogenetics plays a key role in the understanding of such a diverse response. In order to investigate whether functional polymorphisms in proinflammatory cytokine genes (IL-1α, IL-1β, IL-1RN; IL-6 and TNF-α) may i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Unfortunately, no significant predictive value for diagnosis was found. However, Rubino et al firstly used pharmacogenetic methods to confirm that TNF-α polymorphisms in gene function significantly modulated the clinical response to NSAID administration during acute migraine attacks, further supporting the role of the pro-inflammatory cytokine TNF-α in the pathophysiological mechanism of migraine attack ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no significant predictive value for diagnosis was found. However, Rubino et al firstly used pharmacogenetic methods to confirm that TNF-α polymorphisms in gene function significantly modulated the clinical response to NSAID administration during acute migraine attacks, further supporting the role of the pro-inflammatory cytokine TNF-α in the pathophysiological mechanism of migraine attack ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of cytokines suggests that TNF-α and other cytokines are involved not only in the risk of migraine [104][105][106]119] but also in the pathophysiology during attacks [111]. Furthermore, comprehensive genetic analysis using GWAS has identified not only genes encoding CGRP and 5-HT1F receptors but also genes involved in the production of TNF-α and IL-6 and regulating apoptosis and inflammatory responses as candidate genes for migraine [115,116].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of sites in linkage disequilibrium with variants including rs1800629 aimed at resolving previously reported discrepancies and showed that the LTA gene haplotype was associated with migraine risk in Koreans [110]. In addition, pharmacogenetics showed that the efficacy of NSAIDs was significantly lower in migraine attacks in rs1800629 carriers [111], suggesting that rs1800629 may be deeply involved in the pathophysiology of migraine attacks as well as in the risk of migraine. The reproducibility of the results is expected to be reported.…”
Section: Cytokines and Geneticsmentioning
confidence: 99%